Realisasi Kinerja Tenaga Administrasi Sekolah dalam Peningkatan Mutu Pelayanan - Mohammad Muspawi; Hafizahtul Robi'ah (Universitas Negeri Malang, 2020)
Abstract: This research aims to find out the efforts of administrative staff in improving the quality of school services in SMP Negeri 8 Jambi City, and to find out the supporting and inhibiting factors in improving the quality of services at the school. Using descriptive qualitative methods. The subjects of the study were the school principal, the head of the administrative staff and the school administrative staff. Data obtained by interview, observation, documentation. All data were analyzed with a descriptive analysis approach. The results showed: (1) The efforts of administrative staff in improving the quality of school services in SMP Negeri 8 Jambi City were carried out in a systematic process, namely the management of school administrative staff involving teachers and staff to hold joint meetings in order to submit school service reports. This effort was made in accordance with aspects of school needs. (2) Supporting factors for improving the quality of this service is that each administrative staff has their own computer, then the available facilities, the principal always strives to meet the needs of the school. The obstacle faced by school administrative staff in improving the quality of school services is the lack of administrative personnel.Abstrak: Penelitian ini bertujuan untuk mengetahui upaya tenaga administrasi dalam meningkatkan mutu pelayanan sekolah di SMP Negeri 8 Kota Jambi, dan untuk mengetahui faktor pendukung dan penghambat dalam meningkatkan mutu pelayanan di sekolah tersebut. Menggunakan metode kualitatif deskriptif. Subjek penelitian adalah kepala sekolah, kepala tenaga administrasi dan staf tenaga administrasi sekolah. Data diperoleh dengan cara wawancara, observasi, dokumentasi. Semua data dianalisis dengan pendekatan analisis deskriptif. Hasil penelitian menunjukkan: (1) Upaya tenaga administrasi dalam meningkatkan mutu pelayanan sekolah di SMP Negeri 8 Kota Jambi dilakukan dengan proses yang sistematis, yaitu pengelola tenaga administrasi sekolah melibatkan para guru dan staf untuk mengadakan rapat bersama dalam rangka menyampaikan laporan pelayanan sekolah. Upaya ini dibuat sesuai dengan aspek-aspek kebutuhan sekolah. (2) Faktor pendukung peningkatan mutu pelayanan ini yaitu bahwa setiap tenaga administrasi sudah memiliki komputer sendiri, kemudian fasilitas yang tersedia, kepala sekolah selalu mengupayakan untuk memenuhi kebutuhan sekolah. Hambatan yang dihadapi tenaga administrasi sekolah dalam meningkatkan mutu pelayanan sekolah yaitu masih kurangnya jumlah personil tenaga administrasi.